2001
DOI: 10.1007/s003590000165
|View full text |Cite
|
Sign up to set email alerts
|

Responses of a population of antennal olfactory receptor cells in the female moth Manduca sexta to plant-associated volatile organic compounds

Abstract: Extracellular electrophysiological recordings were made from individual type-A trichoid sensilla on the antenna of the female sphinx moth Manduca sexta. A single annulus of the antenna bears about 1,100 of these sensilla, and each is innervated by two olfactory receptor cells. We tested the responses of these receptor cells to a panel of 102 volatile compounds, as well as three plant-derived odor mixtures, and could discern three different functional types of type-A trichoid sensilla. One subset of receptor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 0 publications
6
96
0
Order By: Relevance
“…1) were as follows: ocimene (3,7-dimethyl-1,3,6-octatriene; catalog #74730; ϳ95% pure; mixture of isomers) from Fluka (Buchs, Switzerland); benzyl alcohol (catalog #30519-7; 99.8% pure), cis-3-hexenyl butyrate (catalog #W340200; Ͼ98%), geraniol (trans-3,7-dimethyl-2,6-octadien-1-ol; catalog #G-5135; 98%), hexan-1-ol (catalog #47142; 99%; hereinafter referred to as hexanol), (Ϯ)linalool [(Ϯ)3,7-dimethyl-1,6-octadien-3-ol; catalog #L2602; 97% pure], methyl salicylate (methyl 2-hydroxybenzoate; catalog #240826; Ͼ99%), nerol (cis-3,7-dimethyl-2,6-octadien-1-ol; catalog #26890-9; 97%), nonanal (catalog #76310; Ͼ95%), phenylacetaldehyde (catalog #P0145; 95% pure), trans-2-hexenal (catalog #132659; 98% pure) from Sigma-Aldrich (St. Louis, MO); and cis-3-hexenyl acetate (c3HA) (catalog #H2137; Ͼ97%), cis-3-hexenyl propionate (catalog #P858; Ͼ97%), and cis-3-hexenyl benzoate (catalog #B1039; Ͼ98%) from Tokyo Chemical Industries (Tokyo, Japan). These compounds are found among the volatiles emitted by host plants of Manduca (Loughrin et al, 1990;Fraser et al, 2003;Raguso et al, 2003) and have been shown to evoke responses from the antenna (Fraser et al, 2003) (C. E. Reisenman, unpublished observations) and/or from olfactory receptor cells (ORCs) in trichoid type-A antennal sensilla in females (Shields and Hildebrand, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…1) were as follows: ocimene (3,7-dimethyl-1,3,6-octatriene; catalog #74730; ϳ95% pure; mixture of isomers) from Fluka (Buchs, Switzerland); benzyl alcohol (catalog #30519-7; 99.8% pure), cis-3-hexenyl butyrate (catalog #W340200; Ͼ98%), geraniol (trans-3,7-dimethyl-2,6-octadien-1-ol; catalog #G-5135; 98%), hexan-1-ol (catalog #47142; 99%; hereinafter referred to as hexanol), (Ϯ)linalool [(Ϯ)3,7-dimethyl-1,6-octadien-3-ol; catalog #L2602; 97% pure], methyl salicylate (methyl 2-hydroxybenzoate; catalog #240826; Ͼ99%), nerol (cis-3,7-dimethyl-2,6-octadien-1-ol; catalog #26890-9; 97%), nonanal (catalog #76310; Ͼ95%), phenylacetaldehyde (catalog #P0145; 95% pure), trans-2-hexenal (catalog #132659; 98% pure) from Sigma-Aldrich (St. Louis, MO); and cis-3-hexenyl acetate (c3HA) (catalog #H2137; Ͼ97%), cis-3-hexenyl propionate (catalog #P858; Ͼ97%), and cis-3-hexenyl benzoate (catalog #B1039; Ͼ98%) from Tokyo Chemical Industries (Tokyo, Japan). These compounds are found among the volatiles emitted by host plants of Manduca (Loughrin et al, 1990;Fraser et al, 2003;Raguso et al, 2003) and have been shown to evoke responses from the antenna (Fraser et al, 2003) (C. E. Reisenman, unpublished observations) and/or from olfactory receptor cells (ORCs) in trichoid type-A antennal sensilla in females (Shields and Hildebrand, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Mixture A was identical to the five-component mixture but without linalool (table 1). To further test the effectiveness of (þ)-linalool as an attractant for oviposition, we prepared a synthetic mixture (mixture B, The same concentration of either (2) responses in M. sexta olfactory receptor cells (Shields & Hildebrand 2000). The components of mixture B were pseudo-randomly selected from among those of the D. wrightii floral scent to be different from, but to represent the chemical classes of, the FVs in mixture A (i.e.…”
Section: (B) Feeding Experimentsmentioning
confidence: 99%
“…Specific olfactory receptor cells of M. sexta females have been shown to respond to benzyl alcohol, benzyl benzoate, methyl benzoate and methyl salicylate but no receptor cells were found for eugenol and isoeugenol (Shields and Hildebrand 2001). EAG-recordings from the nocturnal hawk moth Sphinx perelegans (Raguso and Light 1998) yielded preferentially strong responses to the same three compounds, but benzaldehyde elicited a stronger response from the S. perelegans antennae than benzyl alcohol and methyl benzoate, the opposite of what was found here for M. sexta.…”
Section: P Axillaris Flower Emission Is Nocturnal and Controlled By mentioning
confidence: 99%
“…Work on the neurobiology of M. sexta olfaction dates back 30 years, comprising studies on interneurons in the brain (Itagaki and Hildebrand 1990), detection of sex pheromone components by olfactory receptor neurons (Kalinova´et al 2001), antennal olfactory receptor cells responses (Shields and Hildebrand 2001), glomerular organization of antennal lobes (Hildebrand 1996) and their importance for odour-modulated flight (Willis et al 1995). Some information also exists on the learning capability of this hawk moth species (Daly and Smith 2000;Daly et al 2001).…”
Section: Introductionmentioning
confidence: 99%